Theory Of Allophones - Tara Arini; Yani lubis; Rahmi Pitriyani (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The phoneme theory is a well-known phonological theory from the late 19th century (1870) which aims to find out the abstract representation of the phonemes of a given language. To find out whether a phoneme is a phoneme, a phonemic analysis rule is used that states: (1) mutually exclusive neighborhood of complementary distribution, known as the allophone of the same phoneme, (2) a phone in a minimal pair, known as the different phoneme, like /p/ and /b/,(3) a phone in an environment analogous to, like for example /Z/, (4) a phone as a free variant is not another phoneme, but a variation of a phoneme of /c/ the phonemes /č/ and /čh/ are variations of the phoneme /č/. A prosodic phoneme is recognized by a toneme and a chronoma. Daniel Jones' consonant and vowel analysis rule proved inadequate to solve all consonantrelated problems. Trubetskoy and Jacobson made a breakthrough in analyzing a phoneme by a distinguisher and a contrast. The analyzed componentsare: opposition system, bilateral and multilateral opposition system, prepositional opposition system and emotional opposition including the formation of neutralized phonemes and archiephonemes in German.